2014
DOI: 10.1128/aac.02818-13
|View full text |Cite
|
Sign up to set email alerts
|

NDM-5 Carbapenemase-Encoding Gene in Multidrug-Resistant Clinical Isolates of Escherichia coli from Algeria

Abstract: c Here, we report the first autochthonous cases of infections caused by bla NDM-5 New Delhi metallo-␤-lactamase-producing Escherichia coli strains recovered from urine and blood specimens of three patients from Algeria between January 2012 and February 2013. The three isolates belong to sequence type 2659 and they coexpress bla CTX-M-15 with the bla TEM-1 and bla aadA2 genes. Escherichia coli is one of the most common causative agents of infection in humans, and the emergence of resistance to thirdgeneration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 11 publications
3
35
0
Order By: Relevance
“…Our study confirms the emergence of NDM-4-and NDM-5-producing bacteria in the African continent after their recent identification in Cameroon and Algeria, respectively (3,10). The worldwide emergence of NDM-4 and NDM-5 producers is quite alarming, particularly when the increased carbapenemase activity of NDM-4 and NDM-5, compared with that of NDM-1, is taken into account.…”
supporting
confidence: 71%
“…Our study confirms the emergence of NDM-4-and NDM-5-producing bacteria in the African continent after their recent identification in Cameroon and Algeria, respectively (3,10). The worldwide emergence of NDM-4 and NDM-5 producers is quite alarming, particularly when the increased carbapenemase activity of NDM-4 and NDM-5, compared with that of NDM-1, is taken into account.…”
supporting
confidence: 71%
“…Interestingly, 1 isolate (Vir-14) was positive for all of the 4 tested ESBL and carbapenemases. Since the first description of NDM, several variants of the gene have been reported [31]. More recently, 7 NDM (1-7) variants were described from an Indian health care center [29].…”
Section: Discussionmentioning
confidence: 99%
“…The New Delhi metallo-␤-lactamase (NDM) was first described in 2008 (1) and has become one of the most widespread carbapenemases in the world (2)(3)(4). Meanwhile, since the recent discovery of the plasmid-mediated colistin resistance gene mcr-1 in China (5), several studies have confirmed its dissemination in different humans and animals (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%